Meningkatkan Hasil Belajar Food Labels Melalui Media Gambar Peserta Didik - Bawono Pratomo Putro, Ambar (Lembaga Bale Literasi, 2023)
This research aims to enhance the learning outcomes of Food Labels among students at SMP Negeri 1 Batukliang Utara by incorporating visual aids, specifically using images as a learning medium. The researcher seeks to determine whether the use of visual aids, in the form of images, can improve students' learning outcomes of food labels. The researcher supports the implementation of image-based media as a supplementary tool for learning to enrich the educational experience and positively influence learning outcomes. The chosen methodology is Action Research with two cycles, each comprising planning, implementation, observation, and reflection. The experimental design involves dividing the students into an experimental group (receiving instruction with image-based learning) and a control group (participating in conventional learning). Evaluation is conducted to assess the differences in learning outcomes between the two groups to determine the effectiveness of using visual aids. The results of the action research indicate that visual aids effectively enhance the learning outcomes of Food Labels among students in Class IX C at SMPN 1 Batukliang Utara. As a recommendation, the researcher suggests that teachers facing similar challenges consider implementing visual aids to improve learning outcomes. Additionally, teachers are encouraged to create visually appealing and varied images to maximize the effectiveness of the learning process.